Retrospective Analysis of Patients With Prostate Cancer Initiating GnRH Agonists/Antagonists Therapy Using a German Claims Database: Epidemiological and Patient Outcomes - Hupe, Marie C.; Hammerer, Peter; Ketz, Miriam; Kossack, Nils; Colling, Christiane; Merseburger, Axel S. (Frontiers in Oncology, 2018)
Objective: The objective of this study was to obtain real-world information on gonadotropin-releasing hormone agonist/antagonist (GnRHa) therapy in patients with advanced prostate cancer (PCa). Materials and methods: Anonymized, routine healthcare claims data from approx. 75 German statutory health insurance funds from 2010–2015 (n=4,205,227) were analyzed. Patients had an enrolment of 1 year before GnRHa, 1 index quarter of initial GnRHa prescription and ≥2 years of follow-up. Results: In total, 2,382 patients with PCa were eligible. The most frequent index therapy was leuprolide in 56.6%. The rank order of PCa comorbidity prevalence was consistent over time (% at index and 3-years of follow-up): hypertension (71.5; 85.0), hyperlipidemia (45.2; 60.8), cardiovascular disease (CVD) (35.7; 54.1) and diabetes (28.3; 36.2). Comparing pooled therapy classes (agonists, hybrids and antagonist), no significant differences in the incidence of CVD or diabetes were observed. For hypertension, there was a significant increase for agonists (16.4%) compared to antagonists (6.9%, p=0.022) and leuprolide hybrid group (11.6%, p=0.006). During the follow-up period 23.9% of all PCa patients died. There were no significant differences concerning mortality rate and discontinuation rates between the cohorts. In total, 11.0% of all patients discontinued GnRHa after first prescription; the mean time to first switch to another GnRHa therapy was 100 days earlier for hybrids than for agonists (p=0.016). Conclusion: This comparative retrospective analysis provides real-world information about healthcare characteristics and treatment patterns, highlighting the impact of different GnRHa on clinical outcomes for patients with advanced PCa in Germany.